Editorial: Religious heritage: Sites, people, challenges - Volzone, R.; Fontes, J. L.; Lindblad, H. (CIDADES, Comunidades e Territórios, 2025)
Religious heritage can be understood as an intricate synthesis of both tangible and intangible dimensions. From hermitages and chapels to churches, mosques, synagogues, convents, and monasteries, physical sites – often deeply embedded in urban, peri-urban or rural contexts – serve as vessels for spiritual practices, craftsmanship and oral traditions. These structures and customs, together, represent deeply histories of belief, identity, and community.